Hole transport layer and preparation method thereof, perovskite solar cell and preparation method thereof, and solar cell module
By introducing the doping method of PEDOT:PSS, LAD and water into perovskite solar cells, the stability problems caused by Li-TFSI and TBP doping are solved, the efficiency and stability of the battery are improved, and the perovskite solar cell is promoted. The commercialization process of solar cells.
Patent Information
- Application Number
- CN202411461867.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
In existing perovskite solar cells, unreacted reactants and/or harmful by-products are left in the Li-TFSI and TBP-doped Spiro-OMeTAD layer, affecting the stability of the battery.
Instead of LI-TFSI and TBP in Spiro-Altad, the introduction of polygage (3,4-Bye peony): polystyrene sulfonic acid) Boron (LAD) and water, prepare the empty acupoint transmission layer.
The migration rate of SPIRO-Metad as the carrier of the cavity transmission layer has been improved, and the efficiency and stability of the perovskite solar cells are improved. It is suitable for small and large-scale perovskite solar cell components.
Smart Images

Figure CN119365037A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a hole transport layer and a preparation method thereof, a perovskite solar cell and a preparation method thereof, and a solar cell module. Background Art
[0002] The existing perovskite solar cells with the formal structure nip are usually: conductive substrate / electron transport layer / perovskite light absorbing layer / hole transport layer / electrode, among which the hole transport layer often uses 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD). When preparing the hole transport layer Spiro-OMeTAD layer, lithium bis(trifluoromethylsulfonyl)imide (Li-TFSI) and (4-tert-butylpyridine) (TBP) are usually doped into the Spiro-OMeTAD solution to improve the conductivity. However, the instability of Spiro-OMeTAD doped with Li-TFSI and TBP reduces the stability of the overall photovoltaic cell and hinders the commercialization of perovskite solar cells. This instability is caused by ion migration, and the hygroscopic and corrosive properties of Li-TFSI and TBP exacerbate this instability. Spiro-OMeTAD alone has a high glass transition temperature (Tg) of over 120°C, can form a stable solid state, and meets the stability criteria of perovskite photovoltaics. However, the doping process of Li-TFSI and TBP usually forms p-type doping after being exposed to air for several days, which will leave unreacted reactants and / or harmful byproducts in the Li-TFSI and TBP doped Spiro-OMeTAD layer, affecting the stability of perovskite solar cells. Summary of the invention
[0003] Based on this, it is necessary to provide a hole transport layer and its preparation method, a solar cell and its preparation method, and a solar cell module to address the above-mentioned technical problems, so as to solve the problem that unreacted reactants and / or harmful by-products are left in the Li-TFSI and TBP-doped Spiro-OMeTAD layers of existing perovskite solar cells, affecting the stability of the perovskite solar cells.
[0004] The present invention provides a method for preparing a hole transport layer, comprising the following steps:
[0005] 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), tri(pentafluorophenyl)borane (LAD) and water are added to a toluene solution and mixed, and stirred for a preset time to obtain a spin coating liquid; the spin coating liquid does not contain Li-TFSI and TBP; the spin coating liquid is dropped onto a substrate for spin coating, and heated and annealed after spin coating to obtain a hole transport layer for a perovskite solar cell.
[0006] Optionally, the concentration of tris(pentafluorophenyl)borane (LAD) in the spin coating solution is 2 mg / mL-6 mg / mL.
[0007] Optionally, the volume ratio of water in the spin coating solution is 0.01%-0.02%; the volume ratio of the poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS) in the spin coating solution is 20%-80%.
[0008] Optionally, the concentration of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in the spin coating solution is 8 mg / mL-32 mg / mL.
[0009] Optionally, the preset time is 24 hours.
[0010] Optionally, the spin coating conditions include: a rotation speed of 2000-4000 rpm, a time of 30 seconds, and annealing at 110° C. for 10 minutes.
[0011] The present invention provides a hole transport layer, including the hole transport layer prepared by the preparation method of the hole transport layer as described above.
[0012] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps: depositing an electron transport layer, a perovskite light absorption layer, a hole transport layer as described above, and an electrode on a substrate surface. The hole transport layer can be directly spin-coated on the perovskite layer, or a modified layer can be prepared on the perovskite layer and then the hole transport layer can be spin-coated.
[0013] The substrate is selected from any one of indium tin oxide ITO glass, fluorine-doped tin oxide FTO glass and a flexible substrate. The electron transport layer material is selected from SnO2, ZnO, Al2O3, TiO2, ICBA and C 60 The electrode includes a metal electrode and / or a non-metal electrode, the metal electrode includes silver, gold or aluminum, and the non-metal electrode includes a carbon electrode, tungsten-doped indium oxide IWO, fluorine-doped tin oxide FTO or indium tin oxide ITO.
[0014] Perovskite is represented by the chemical formula ABX3, where the A position is composed of inorganic Cs + Cationic, organic methylamine (abbreviated as MA + , molecular formula is CH3NH 3+ ) and formamidine (FA + , molecular formula is HC(NH2) 2+ ) cations; the B position belongs to inorganic cations, such as Sn 2+ and Pb 2+ ; The X position represents a halogen ion, such as I ﹣ , Cl ﹣ Br ﹣ . B and X are connected to form an octahedron [BX6] 4﹣ The structure of the A-site cation is located at the center of the structure. The precursor material for preparing the perovskite layer includes metal halide and / or organic halide, and the metal halide material is selected from any one or more of lead iodide PbI2, lead chloride PbCl2, lead bromide PbBr2, cesium iodide CsI2, cesium bromide CsBr2, cesium chloride CsCl2, tin iodide SnI2, tin bromide SnBr2 and tin chloride SnCl2. The organic halide material is selected from any one or more of methylamine iodide FAI, methylamine iodine MAI, methylamine chloride FACl, methylamine chloride MACl, methylamine bromide FABr and methylamine bromide MABr.
[0015] The present invention provides a perovskite solar cell, including a perovskite solar cell prepared by the method for preparing a perovskite solar cell as described above.
[0016] The present invention provides a solar cell module, comprising the perovskite solar cell as described above.
[0017] In the present invention, Spiro-OMeTAD doped with LAD, PEDOT:PSS and water is called SPL (SPL is the spin coating liquid prepared by the present invention), Spiro-OMeTAD doped with Li-TFSI and TBP is called Li-Spiro, the perovskite solar cell prepared with SPL film as the hole transport layer is called SPL cell, and the perovskite solar cell prepared with Li-Spiro film as the hole transport layer is called Li-Spiro cell.
[0018] Compared with the traditional method, the present invention has the following beneficial effects:
[0019] The present invention does not dope the existing Li-TFSI and TBP into Spiro-OMeTAD, but introduces poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), tri(pentafluorophenyl)borane (LAD) and water, thereby improving the carrier mobility of Spiro-OMeTAD as a hole transport layer. At the same time, it is used in perovskite solar cells to improve the efficiency and stability of the cells. Whether it is a small-area cell or a large-area component, the perovskite solar cell prepared by the method of the present invention has excellent stability, which will be beneficial to the commercialization of perovskite solar cells and promote the industrialization progress of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0021] Figure 1 is a graph showing the photovoltaic performance and cell stability test results of a perovskite solar cell in an embodiment of the present invention;
[0022] Figure 2 It is a photovoltaic safety characteristic curve diagram of a conventionally prepared Li-Spiro cell and a perovskite solar cell (SPL cell) in an embodiment of the present invention;
[0023] Figure 3 The aperture area in the embodiment of the present invention is 0.06 cm 2 Certification results of perovskite solar cells (SPL cells);
[0024] Figure 4 The aperture area in the embodiment of the present invention is ~1cm 2 Certification results of perovskite solar cells (SPL cells);
[0025] Figure 5 The thermal stability test results of the hole transport layer of the conventionally prepared Li-Spiro battery and the thermal stability test results of the hole transport layer of the perovskite solar cell (SPL battery) in the embodiment of the present invention are shown;
[0026] Figure 6 are the UV photoelectron spectra (UPS) of perovskite, Li-Spiro, and SPL films, and the energy level diagrams of perovskite, Li-Spiro, and SPL films;
[0027] Figure 7Color change of the hole transport layer deposited on the perovskite substrate over time after heat aging at 85°C for 1000 hours in an embodiment of the present invention (SEM image);
[0028] Figure 8 Atomic force microscopy image of a hole transport layer deposited on a perovskite substrate after heat aging at 85°C for 200 hours in an embodiment of the present invention;
[0029] Fig. 9 The pore area of Spiro-OMeTAD doped with different concentrations of PEDOT:PSS in the present invention is ~0.06cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery;
[0030] Fig.10 The pore area of the Spiro-OMeTAD doped with 20% PEDOT:PSS and different concentrations of LAD in the embodiment of the present invention is 0.06 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery;
[0031] Fig.11 The pore area of Spiro-OMeTAD doped with 20% PEDOT:PSS, 4 mg / mL LAD and different concentrations of water in the embodiment of the present invention is 0.06 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery;
[0032] Fig.12 The pore area of Spiro-OMeTAD doped with 20% PEDOT:PSS, 4 mg / mL LAD and 0.01% water at different concentrations is ∼0.06 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery;
[0033] Fig.13 The aperture area of the conventionally prepared Li-Spiro cell and the perovskite solar cell (SPL cell) in the embodiment of the present invention is 0.06 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery;
[0034] Fig.14 The aperture area of the conventionally prepared Li-Spiro cell and the perovskite solar cell (SPL cell) in the embodiment of the present invention is 1 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery;
[0035] Fig.15 The aperture area of the conventionally prepared Li-Spiro cell and the perovskite solar cell (SPL cell) in the embodiment of the present invention is 29 cm 2 Statistical diagram of photovoltaic characteristic parameters of battery modules. DETAILED DESCRIPTION
[0036] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0037] The preparation method of the traditional Li-Spiro solution is as follows: 73.5 mg of Spiro-OMeTAD, 25.0 μL tBP, 17.0 μL Li-TFSI (520 mg dissolved in 1 mL acetonitrile), and 8.0 μL FK 209Co(III)TFSI (360 mg dissolved in 1.0 mL acetonitrile) are dissolved in 1.0 mL chlorobenzene to form a Li-Spiro solution.
[0038] The present invention provides a method for preparing a hole transport layer, comprising the following steps:
[0039] 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), tri(pentafluorophenyl)borane (LAD) and water are added to a toluene solution and mixed, and stirred for 24 hours to obtain a spin coating liquid; the spin coating liquid does not contain Li-TFSI and TBP; the spin coating liquid is dropped onto a substrate for spin coating, the spin coating speed is 2000-4000 rpm, and annealed at 110°C for 10 minutes after spin coating to obtain a hole transport layer for a perovskite solar cell.
[0040] Compared with the traditional method for preparing the hole transport layer, the present invention does not dope Li-TFSI and TBP in Spiro-OMeTAD, but introduces poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), tri(pentafluorophenyl)borane (LAD) and water. Figures 1 to 15 The results show that the present invention improves the carrier mobility of the hole transport layer Spiro-OMeTAD and the stability of the photovoltaic device. It ensures that the electrical properties of the Spiro-OMeTAD transport layer can still be maintained without doping Li-TFSI and TBP, thereby improving the stability of the perovskite solar cell.
[0041] Optionally, the substrate may be a perovskite layer or a modified layer spin-coated on the perovskite layer; the hole transport layer of the present invention may be directly spin-coated on the perovskite layer, or the hole transport layer of the present application may be spin-coated after preparing a modified layer on the perovskite layer.
[0042] Optionally, the concentration of tri(pentafluorophenyl)borane (LAD) in the spin coating solution is 2 mg / mL-6 mg / mL; specifically, the concentration of tri(pentafluorophenyl)borane (LAD) can be 2 mg / mL,
[0043] One of 3mg / mL, 4mg / mL, 5mg / mL or 6mg / mL, of which 4mg / mL has the best effect. For test results, see Fig.10 ,.
[0044] Optionally, the volume ratio of water in the spin coating liquid is 0.01%-0.02%; specifically, the volume ratio of water in the spin coating liquid is 0.01%, and the best effect is achieved. The test results are shown in Fig.11 .
[0045] Optionally, the volume ratio of PEDOT:PSS in the spin coating solution is 20% to 80%; specifically, the volume ratio of water in the spin coating solution is 20%, 40%, 60% or 80%, among which 20% has the best effect. The test results are shown in Fig. 9 .
[0046] Optionally, the concentration of Spiro-OMeTAD in the spin coating solution is 8 mg / mL-32 mg / mL; specifically, the concentration of Spiro-OMeTAD in the spin coating solution is one of 8 mg / mL, 16 mg / mL, 24 mg / mL or 32 mg / mL, wherein the concentration of 16 mg / mL has the best effect, and the test results are shown in Fig.12 .
[0047] The rotation speed of the spin coating in the present invention is 2000-4000 rpm; the specific rotation speed is one of 2000 rpm, 3000 rpm or 4000 rpm, among which 3000 rpm has the best effect.
[0048] For ease of understanding, in the present invention, Spiro-OMeTAD doped with tri(pentafluorophenyl)borane (LAD), PEDOT:PSS and water is referred to as SPL (SPL is the spin coating liquid prepared by the present invention, the same below), Spiro-OMeTAD doped with Li-TFSI and TBP is referred to as Li-Spiro, the perovskite solar cell prepared with SPL film as the hole transport layer is referred to as SPL cell, and the perovskite solar cell prepared with Li-Spiro film as the hole transport layer is referred to as Li-Spiro cell.
[0049] The present invention provides a hole transport layer, including the hole transport layer prepared by the preparation method of the hole transport layer as described above.
[0050] The preparation method of the Spiro-OMeTAD hole transport layer of the present invention is used for small-area perovskite solar cells and also for large-area perovskite solar cell modules, see Figure 1-Figure 15 In Spiro-OMeTAD, the existing Li-TFSI and TBP are not doped, but poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS), tri(pentafluorophenyl)borane (LAD) and water are introduced, which improves the carrier mobility of Spiro-OMeTAD as a hole transport layer. At the same time, it is used in perovskite solar cells to improve the efficiency and stability of the device. Whether it is a small-area device or a large-area component, the perovskite solar cell prepared by the method of the present invention has excellent stability, which will be beneficial to the commercialization of perovskite solar cells and promote the industrialization progress of perovskite solar cells.
[0051] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps: depositing an electron transport layer, a perovskite light absorption layer, a hole transport layer as described above, and an electrode on a substrate surface. The hole transport layer can be directly spin-coated on the perovskite layer, or a modified layer can be prepared on the perovskite layer and then the hole transport layer can be spin-coated.
[0052] The substrate is selected from any one of indium tin oxide ITO glass, fluorine-doped tin oxide FTO glass and a flexible substrate. The electron transport layer material is selected from SnO2, ZnO, Al2O3, TiO2, ICBA and C 60 The electrode includes a metal electrode and / or a non-metal electrode, the metal electrode includes silver, gold or aluminum, and the non-metal electrode includes a carbon electrode, tungsten-doped indium oxide IWO, fluorine-doped tin oxide FTO or indium tin oxide ITO.
[0053] Perovskite has the chemical formula ABX 3 To represent, the A position is composed of inorganic Cs + Cationic, organic methylamine (abbreviated as MA + , molecular formula is CH 3 NH 3+ ) and formamidine (abbreviated as FA+, with the molecular formula HC(NH2) 2+ ) cations; the B position belongs to inorganic cations, such as Sn 2+ and Pb 2+ ; The X position represents a halogen ion, such as I ﹣ , Cl ﹣ Br ﹣ . B and X are connected to form an octahedron [BX6] 4﹣The precursor material for preparing the perovskite layer includes metal halide and / or organic halide, and the metal halide material is selected from lead iodide PbI2, lead chloride PbCl2, lead bromide PbBr2, cesium iodide CsI2, cesium bromide CsB r2 Any one or more of cesium chloride CsCl2, tin iodide SnI2, tin bromide SnBr2 and tin chloride SnCl2. The organic halide material is selected from any one or more of methylamine iodide FAI, methylamine iodine MAI, methylamine chloride FACl, methylamine chloride MACl, methylamine bromide FABr and methylamine bromide MABr.
[0054] In one embodiment, the SPL cell small area cell structure: FTO glass / dense TiO2 layer (c-TiO2) / dense SnO2 layer (c-SnO2) / Cs 0.05 MA 0.05 FA 0.9 Devices of PbI3 / phenylammonium bromide (PEAI) / hole transport layer (HTL) / MoOx / ITO / Au structure, where MoOx is molybdenum oxide and ITO is indium tin oxide. The patterned FTO substrate (Asahi FTO glass, 1.8 mm, 12-13 Ω / square) was cleaned in an ultrasonic bath with detergent (5% Hellmanex aqueous solution), deionized water, acetone and isopropanol for 15 minutes. The FTO substrate was then further cleaned with ultraviolet ozone (UVO) surface treatment for 15 minutes. A dense TiO2 layer (c-TiO2) and a SnO2 layer (c-SnO2) were sequentially deposited on the cleaned FTO substrate by chemical bath deposition (CBD). The substrate was annealed on a hot plate at 190°C for 60 minutes. A perovskite precursor solution (1.4 M) was prepared by adding 709.9 mg PbI2, 240.8 mg FAI, 33.1 mg MACl and 11.8 mg CsCl to 200 μL DMSO and 800 μL DMF. The solution was stirred at 50°C for 2 hours.
[0055] After UVO treatment of the FTO substrate for 15 minutes, the perovskite precursor solution was spin-coated onto the surface of the FTO / c-TiO2 / c-SnO2 substrate at 1000 rpm for 10 seconds, accelerated to 5000 rpm for 5 seconds, and maintained at this speed for 20 seconds. The process was carried out in a glove box filled with nitrogen. Next, the substrate was placed in a homemade rapid vacuum drying device. After pumping for 20 seconds, a brown transparent perovskite film with a mirror-like surface was obtained. The spin-coated perovskite layer was annealed at 100°C for 1 hour and then at 150°C for 10 minutes. Then, 60 μL of styrylammonium bromide PEAI solution (5 mg / mL in isopropanol) was spin-coated on the perovskite film at a speed of 5000 rpm for 30 seconds. The doped Spiro-OMeTAD solution was then spin-coated at a speed of 3000 rpm for 30 seconds and annealed at 110°C for 10 minutes. A 2nm thick MoOx layer and a 100nm thick ITO layer were sequentially deposited on the doped Spiro-OMeTAD layer. Finally, about 70nm thick gold was evaporated as the back electrode.
[0056] The doped Spiro-OMeTAD solution is a spin coating solution (SPL solution). The solution components are as described in the preparation method of the spin coating solution.
[0057] The present invention provides a perovskite solar cell, including a perovskite solar cell prepared by the method for preparing a perovskite solar cell as described above.
[0058] The present invention provides a solar cell module, comprising the perovskite solar cell as described above.
[0059] In one embodiment, the SPL battery assembly structure is: in size 6.5×7.0cm 2A perovskite solar cell module with 8 subcells connected in series was fabricated on an FTO glass substrate of . The serial interconnection of the module was achieved by P1, P2 and P3 laser scribing, which were patterned using a laser scribing system (Trotec) at 1064nm and 20W power. The FTO substrate was pre-patterned with P1 (width of 40μm) at a speed of 300mm / s, a frequency of 65kHz and a pulse width of 120ns at 60% laser power. The process for preparing the c-TiO2 / c-SnO2 layer is the same as that of the small-area cell of the SPL cell mentioned above. The perovskite precursor deposition and manufacturing process are also the same as those of the small-area cell of the SPL cell mentioned above, except for the concentration of the perovskite precursor. The module uses 1.3M perovskite precursor to prepare the perovskite layer. After the preparation of the perovskite layer, the process parameters for spin coating the PEAI passivation layer and the doped Spiro-OMeTAD layer are the same as those of the small-area cell of the SPL cell. Before the Au evaporation process step, the P2 line (width of 100 μm) was patterned using an average laser power of 15%, a speed of 1000 mm / s, a frequency of 65 kHz, and a pulse duration of 120 ns. A 2 nm thick MoOx layer, a 100 nm thick ITO layer, and a 70 nm thick Au layer were deposited in sequence, and the P3 line (width of 40 μm) was made using the same scribing conditions as the P2 line. The distance between P1 and P3 was about 210 μm, and the geometric fill factor (GFF) was about 96.8%.
[0060] Comparative Example
[0061] Preparation method of Li-Spiro solution: 73.5 mg of Spiro-OMeTAD, 25.0 μL tBP, 17.0 μL Li-TFSI (520 mg dissolved in 1 mL acetonitrile), and 8.0 μL FK 209Co(III)TFSI (360 mg dissolved in 1.0 mL acetonitrile) were dissolved in 1.0 mL chlorobenzene to form a Li-Spiro solution.
[0062] The doped Spiro-OMeTAD solution in the perovskite solar cell of the comparative example is a conventional Li-Spiro solution. The Li-Spiro layer is spin-coated on the substrate from the Li-Spiro solution at a speed of 5000 rpm for 30 seconds. The remaining preparation methods of the Li-Spiro cell and the battery assembly in the comparative example are the same as those of the SPL cell and the battery assembly of the present invention.
[0063] Testing methods and testing equipment:
[0064] The efficiency of the perovskite solar cell in the present invention was measured using a Keithley 2400 source meter under the AM1.5G solar spectrum, and the JV characteristics of the photovoltaic cell were obtained by an Oriel 9600 solar simulator. The designated area of the cell of different sizes was 0.06 cm 2 , 1cm 2 and 29.0cm 2 The central hole is covered with a metal sheet, which corresponds to the active area of the battery, and the corresponding aperture area is ~0.06cm 2 ,~1cm 2 and ~29.0cm 2 The efficiency of cells and battery components. The external quantum efficiency (EQE) was measured under short-circuit conditions using an integrated system (Enlitech) and a lock-in amplifier with a current preamplifier. SEM images of the films were recorded using a field emission scanning electron microscope SEM (Hitachi, S4800). AFM, KPFM and C-AFM were recorded on a scanning probe microscope (Bruker, Dimension ICON). Ultraviolet photoelectron spectroscopy (UPS) measurements were observed using a Kratos AXIS ULTRADALD with a He Iα photon source (hν=21.22 eV) and a 10 V bias.
[0065] Stability test: The packaged cells and battery components were kept in a constant temperature and humidity chamber (GP / TH-150, SH Guangpin Test Equipment Manufacturing Co., Ltd.) under ambient conditions. The JV curve was measured by an electronic system using a 22-bit delta-sigma analog-to-digital converter. A reference silicon photodiode was placed next to the module to record the light intensity. The packaged module was kept at the maximum power point using the maximum power point MPP tracking algorithm under 1 sun illumination according to the ISOS protocol.
[0066] Packaging method: These cells and battery assemblies are encapsulated by glass-to-glass encapsulation technology combined with edge sealant (UV ultraviolet curing sealant, Three bond 3035B), and the module is sealed under ultraviolet light (LED flood light, DELOLUX 20). First, the edge of the device is cleared using a laser. Indium solder is soldered on the FTO electrode and Au electrode at the edge of the battery. Then, the glass is placed on the Au electrode of the cell or battery assembly. The light-curing sealant is deposited on the edge of the glass to completely fill the gap between the top glass and the module. Finally, in the glove box, ultraviolet light is used at 25% of the maximum power for 120 seconds to induce cross-linking and curing of the sealant with the glass.
[0067] Test results:
[0068] like Figure 1As shown, the photovoltaic performance and cell stability of the perovskite solar cell in the embodiment of the present application.
[0069] (a) Aperture area is ~0.06 cm 2 Forward scan (Fwd) and reverse scan (Rev) JV curves and photovoltaic characteristic parameters of SPL cells
[0070] (b) Aperture area is ~1 cm 2 Forward scan (Fwd) and reverse scan (Rev) JV curves and photovoltaic characteristic parameters of SPL cells
[0071] (c) Aperture area is ~29 cm 2 Forward scan (Fwd) and reverse scan (Rev) JV curves and photovoltaic characteristic parameters of SPL solar cell modules
[0072] (d) The encapsulated aperture area is ∼0.06 cm 2 Comparison of the stability of SPL batteries and Li-Spiro batteries under the same environment (85°C, 40%-70% relative humidity, dark state)
[0073] (e) The unencapsulated aperture area is ~1 cm 2 Comparison of the stability of SPL batteries and Li-Spiro batteries under the same environment (25-35°C, 40%-70% relative humidity, dark state)
[0074] (f) The aperture area of the package is ~29 cm 2 Comparison of the stability of SPL battery components and Li-Spiro battery components under the same environment (65℃, 40%-70% relative humidity, 1 sun irradiation)
[0075] The Spiro-OMeTAD layer doped with PEDOT:PSS, LAD and water was used as the hole transport layer to prepare perovskite solar cells, such as Figure 1 The certified efficiencies of the resulting photovoltaic cells are 25.54% (stable at 25.26%), 24.58% (stable at 23.93%), and 22.86% (stable at 22.85%), with cell aperture areas of ~0.06 cm 2 ,~1cm 2 and 29cm 2 . Very close to the current world's highest certified efficiency of 26.7%.
[0076] According to the International Organic Photovoltaic Stability Summit (ISOS) protocol, the prepared battery was tested for stability under ISOS-D-1 (85°C, 40%-70% relative humidity), ISOS-L-2 (~30°C, 40%-70% relative humidity) and ISOS-L-1 (65°C, 40%-70% relative humidity) protocols, and maintained 90.2%, 92.6% and 92.8% of the initial efficiency after 1000, 7000 and 5000 hours, respectively. The corresponding photovoltaic parameters and stability are shown in Figure 2. Figure 1 As shown. Figure 1 It can be seen that the traditional Li-Spiro battery is very unstable and the battery efficiency drops rapidly in a short time. In addition, many preparation methods that are suitable for small-area batteries in this field may not be suitable for large-area batteries. However, in the present invention, whether it is a small area (~0.06cm 2 ) battery or large area component (29cm 2 ), perovskite photovoltaics can maintain good stability, which is crucial for the current industrial application of perovskite solar cells. Therefore, this doping method solves the industry's key requirements for the stability, efficiency and production cost of perovskite solar cells, and improves its commercial prospects.
[0077] like Figure 2 As shown, the photovoltaic safety characteristic curve of the conventionally prepared Li-Spiro battery and the perovskite solar cell (SPL battery) in one embodiment of the present invention; Figure 2 As shown, the efficiency of the Li-Spiro cell is 25.12%, and the efficiency of the SPL cell is 25.86%. It can be seen that the photovoltaic characteristics of the SPL cell of the present invention are not reduced but increased. The method of preparing the hole transport layer Spiro-OMeTAD using the present invention improves the photoelectric conversion efficiency of the perovskite solar cell.
[0078] like Figure 3 , Figure 4 As shown, the certified efficiency of the most efficient perovskite solar cell provided by the present invention is certified by the China National Photovoltaic Industry Metrology and Testing Center (NPVM). Figure 3 The aperture area of the present invention is ~0.06cm 2 The certification results of perovskite solar cells (SPL cells) Figure 4 The aperture area of the present invention is ~1cm 2 Certification results of perovskite solar cells (SPL cells).
[0079] like Figure 5 As shown, the thermal stability of the hole transport layer of the conventionally prepared Li-Spiro battery is compared with the thermal stability of the hole transport layer of the perovskite solar cell (SPL battery) in one embodiment of the present invention.
[0080] (a) Conductive atomic force microscopy (C-AFM) images of spin-coated Li-Spiro and SPL (spin-coating liquid prepared in the present invention) on the perovskite layer before and after thermal aging at 85°C for 200 h.
[0081] (b) Top-down SEM images of spin-coated Li-Spiro and SPL on the perovskite layer before and after aging for 200 h at 85 °C. The red dashed loop indicates a hole formed in the aged Li-Spiro layer.
[0082] (c) Kelvin probe force microscopy (KPFM) images of spin-coated Li-Spiro and SPL on the perovskite layer before and after thermal aging at 85 °C for 200 h.
[0083] like Figure 6 As shown, the energy levels of perovskite, Li-Spiro, and SPL films are compared. (a) Ultraviolet photoelectron spectroscopy (UPS) spectra of perovskite, (b) Li-Spiro, and (c) SPL films with cutoff region (left) and Fermi edge region (right). (d) Energy level diagram of perovskite, Li-Spiro, and SPL films.
[0084] like Figure 5 , Figure 6 As shown in Figure 2, the conductivity of Li-Spiro and SPL films was studied by the resistivity obtained from the current-voltage (IV) curve of the battery configured with FTO / HTL / Au. The conductivity of Li-Spiro film was calculated to be 1×10 7 Scm-1, while the conductivity of the SPL film is 1×10 -5 Scm-1, which is consistent with the findings of conductive atomic force microscopy (c-AFM) images, ref. Figure 5 (a). Compared with the freshly prepared Li-Spiro film, the SPL film shows a brighter and more uniform current map, as well as a higher current distribution. Figure 5 As can be seen in (b), the aged Li-Spiro layer has obvious holes, while the aged SPL layer presents an amorphous and uniform surface morphology without visible pinholes or defects.
[0085] The current-voltage (IV) curve of the FTO / PEDOT:PSS / HTL / Au cell structure was calculated using the space charge limited current (SCLC). The hole mobility of the Li-Spiro and SPL hole transport layers was estimated to be 2.48×10 - 3 cm 2 V -1 s -1 and 5.19×10 -3 cm2 V -1 s -1 , further verifying that the holes in the SPL hole transport layer are more easily transported. At the same time, the highest occupied molecular orbital (HOMO) energy level of the SPL film (-5.14 eV) obtained from the ultraviolet photoelectron spectroscopy (UPS) spectrum is shifted downward relative to the Li-Spiro film (-5.07 eV), which accelerates the transfer of holes from the perovskite to the hole transport layer ( Figure 6 ).
[0086] Figure 7 Shown is the color change of hole transport layers deposited on perovskite films upon thermal aging at 85 °C for 1000 h in a nitrogen atmosphere. (a) Li-Spiro film. (b) SPL film. After 200 h, the Li-Spiro film starts to decompose at the edges and continuous degradation is observed. The SPL film, on the other hand, retains its original color after 1000 h.
[0087] Figure 8 AFM (atomic force microscope) images of Li-Spiro and SPL films deposited on perovskite layers after thermal aging at 85°C for 200 hours are shown. (a) As-prepared Li-Spiro film. (b) Aged Li-Spiro film. (c) As-prepared SPL film. (d) Aged SPL film.
[0088] according to Figure 8 Atomic force microscopy (AFM) images of the aged Li-Spiro film after thermal aging show that the aged Li-Spiro film has many cubic and rod-shaped crystals, as well as a large number of voids, due to the volatilization of TBP and the crystallization of Spiro-OMeTAD. Note that the roughness (Ra) value of the initial SPL film was observed to be 9.1 nm, and the roughness (Ra) value of the initial Li-Spiro film was 10.1 nm. After thermal aging at 85°C for 200 hours, the roughness (Ra) value of the Li-Spiro film increased significantly to 16.7 nm, while the roughness (Ra) value of the SPL film only slightly increased to 11.4 nm. In contrast, the SPL film was able to skillfully maintain its original surface morphology and suppress degradation caused by thermal stress.
[0089] In the present invention Figure 9-13 Small area refers to the pore area of ~0.06cm 2 Perovskite solar cell (SPL cell). Herein, "~" means a value of the aperture area approximately equal to, for example, ~0.06cm 2 The exact value is 0.0599cm 2 ,~0.1cm 2 The exact value is 1.044cm 2At the same time, the designated area for batteries of different sizes has a 0.06cm 2 , 1cm 2 and 29.0cm 2 The efficiency is measured after the metal sheet covering the center hole of the battery. The center hole corresponds to the active area of the battery, and the corresponding aperture area is 0.06 cm2.
[0090] Cells and battery assemblies of ~1cm2 and ~29.0cm2.
[0091] Figures 9 to 12 The statistical distribution of photovoltaic characteristic parameters of optimized doping concentrations of PEDOT:PSS, tris(pentafluorophenyl)borane (LAD) and water in Spiro-OMeTAD. 20 cells were prepared under each condition to demonstrate the reproducibility of the results. The figure consists of a box plot with mean, maximum / minimum values, box boundaries, whiskers and percentiles. Fig. 9 Statistical diagrams of photovoltaic characteristic parameters of small-area SPL cells with Spiro-OMeTAD doped with different concentrations of PEDOT:PSS, (a) short-circuit current, (b) fill factor, (c) open-circuit voltage, and (d) efficiency; the concentrations of PEDOT:PSS are 0%, 20%, 40%, 60%, 80%, and 100%, respectively.
[0092] Fig.10 The photovoltaic characteristic parameter statistics of small-area SPL cells containing 20% PEDOT:PSS and different concentrations of tri(pentafluorophenyl)borane (LAD) doped Spiro-OMeTAD are shown in Figure 2. (a) short-circuit current, (b) fill factor, (c) open-circuit voltage, and (d) efficiency. The concentrations of tri(pentafluorophenyl)borane (LAD) are 0 mg / mL, 2 mg / mL, 4 mg / mL, and 6 mg / mL, respectively. It should be noted that tri(pentafluorophenyl)borane is also referred to as BCF, so Fig.10 It says BCF.
[0093] Fig.11 Statistical graphs of photovoltaic characteristic parameters of small-area SPL cells containing 20% PEDOT:PSS and 4 mg / mL LAD and different concentrations of water doped in Spiro-OMeTAD, (a) short-circuit current, (b) fill factor, (c) open-circuit voltage, and (d) efficiency; the water concentrations are 0%, 0.01%, and 0.02%, respectively.
[0094] Fig.12Statistical graphs of photovoltaic characteristic parameters of small-area SPL cells containing 20% PEDOT:PSS, 4mg / mLL A and 0.01% water doped with different concentrations of Spiro-OMeTAD: (a) short-circuit current, (b) fill factor, (c) open-circuit voltage, and (d) efficiency; the concentrations of Spiro-OMeTAD are 8mg / mL, 16mg / mL, 24mg / mL, and 32mg / mL, respectively.
[0095] according to Figure 9-12 The battery efficiency data of the present invention shows that the battery efficiency of the undoped Spiro-OMeTAD as the hole transport layer is 7.72% on average, and the battery efficiency of the Spiro-OMeTAD containing 20% PEDOT:PSS as the hole transport layer is 23.70% on average. On this basis, after adding 4 mg / mL of LAD, the average battery efficiency is increased to 24.25%, and then after adding 0.01% water, the average efficiency is increased to 24.82%. It can be seen that the doping method of the present invention has better performance than the battery without doping in Spiro-OMeTAD, doping PEDOT:PSS alone, and doping tris(pentafluorophenyl)borane (LAD) alone.
[0096] It can be seen that the SPL film of the present invention has excellent heat resistance, and using it as a hole transport layer of a perovskite solar cell ensures high hole transport capacity, improves efficiency and maintains excellent cell stability.
[0097] in addition, Fig.13 The aperture area of the conventionally prepared Li-Spiro cell and the perovskite solar cell (SPL cell) of the present invention is 0.06 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery; Fig.14 The aperture area of the conventionally prepared Li-Spiro cell and the perovskite solar cell (SPL cell) of the present invention is 1 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery; Fig.15 The aperture area of the conventionally prepared Li-Spiro cell and the perovskite solar cell (SPL cell) of the present invention is 29 cm 2 Statistical diagram of photovoltaic characteristic parameters of the battery module. 20 cells or 20 battery modules were prepared under each condition to prove the repeatability of the results.
[0098] The aperture area is 0.06 cm 2 The comparison of photovoltaic characteristic parameters of the cells is shown in Table 1 below:
[0099]
[0100]
[0101] Aperture area is 1cm 2 The comparison of photovoltaic characteristic parameters of the cells is shown in Table 2 below:
[0102]
[0103] Aperture area: 29cm 2 The photovoltaic characteristic parameters of the battery modules are compared as shown in Table 3:
[0104] The above embodiments are only used to illustrate the technical solution of the present invention, but not to limit it.
[0105] The present invention has been described in detail according to the aforementioned embodiments. Those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a hole transport layer, characterized in that: The following steps are involved: 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid), tri(pentafluorophenyl)borane and water are added to a toluene solution, mixed, and stirred for a preset time to obtain a spin coating solution; the spin coating solution does not contain Li-TFSI and TBP; The spin coating liquid is dropped onto the substrate for spin coating, and then heated and annealed to obtain a hole transport layer for a perovskite solar cell.
2. The preparation method according to claim 1, characterized in that The concentration of tri(pentafluorophenyl)borane in the spin coating solution is 2 mg / mL-6 mg / mL.
3. The preparation method according to claim 1, characterized in that: The volume ratio of the water in the spin coating liquid is 0.01%-0.02%; the volume ratio of the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) in the spin coating liquid is 20%-80%.
4. The preparation method according to claim 1, characterized in that: The concentration of the 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in the spin coating solution is 8 mg / mL-32 mg / mL.
5. The preparation method according to claim 1, characterized in that: The preset time is 24 hours.
6. The preparation method according to claim 1, characterized in that: The spin coating conditions include: a rotation speed of 2000-4000 rpm, a time of 30 seconds, and annealing at 110° C. for 10 minutes.
7. A hole transport layer, characterized in that: A hole transport layer prepared by the method for preparing a hole transport layer according to any one of claims 1 to 6.
8. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: An electron transport layer, a perovskite light absorption layer, a hole transport layer as claimed in claim 7 and an electrode are deposited on the surface of the substrate.
9. A perovskite solar cell, characterized in that: A perovskite solar cell prepared by the method for preparing a perovskite solar cell according to claim 8.
10. A solar cell module, characterized in that: Includes the perovskite solar cell as described in claim 9.